The city school general knowledge level 1 - Mansoor, Rabia (The City School Albakio International Lahore, 2012)
The City School's general knowledge curriculum covers a wide range of topics designed to broaden students' understanding of the world around them. It typically includes subjects like history, geography, science, current events, and cultural studies. The program encourages critical thinking, curiosity, and awareness of global issues, helping students make connections between different fields of knowledge. Activities often involve interactive discussions, projects, and quizzes to engage students and enhance their learning experience.